Insights in the glycosylation steps during biosynthesis of the antitumor anthracycline cosmomycin: characterization of two glycosyltransferase genes - Garrido, Leandro M. (2006)
Glycosylation pattern in cosmomycins is a distinctive feature among anthracyclines. These antitumor compounds possess two trisaccharide chains attached at C-7 and C-10, each of them with structural variability, mainly at the distal deoxysugar moieties. We have characterized a 14-kb chromosomal region from Streptomyces olindensis containing 13 genes involved in cosmomycin biosynthesis. Two of the genes, cosG and cosK, coding for glycosyltransferase were inactivated with the generation of five new derivatives. Structural elucidation of these compounds showed altered glycosylation patterns indicating the capability of both glycosyltransferases of transferring deoxysugars to both sides of the aglycone and the flexibility of CosK with respect to the deoxysugar donor. A model is proposed for the glycosylation steps during cosmomycins biosynthesis.